Democratic Republic of the Congo : Second Review Under the Three-Year Arrangement Under the Extended Credit Facility and Financing Assurances Review-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Democratic Republic of the Congo. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The IMF's Executive Board completed the first review under the Extended Credit Facility (ECF) arrangement in June 2010 and decided that the Democratic Republic of Congo (DRC) had reached the completion point under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative. In 2010, an improvement in global economic conditions supported strong macroeconomic performance; however, weaknesses in the financial sector were also exposed. The authorities recognized the importance of strengthening the independence and effectiveness of the central bank to sustain low and stable inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet